Production of Biomass Crops Using Biowastes on Low‐Fertility Soil: 1. Influence of Biowastes on Plant and Soil Quality. Issue 6 (1st November 2016) - Esperschuetz, J.; Anderson, C.; Bulman, S.; Lense, O.; Horswell, J.; Dickinson, N.; Hofmann, R.; Robinson, B. H.
Abstract : Land application of biosolids to low‐fertility soil can improve soil quality by increasing concentrations of macronutrients and trace elements. Mixing biosolids with sawdust could reduce the risks of contaminant accumulation posed by rebuilding soils using biosolids alone. We aimed to determine the effects of biosolids and biosolids‐sawdust on the plant quality and chemical composition of sorghum, rapeseed, and ryegrass. Plants were grown in a greenhouse over a 5‐mo period in a low‐fertility soil amended with biosolids (1250 kg N ha −1 ), biosolids‐sawdust (0.5:1), or urea (200 kg N ha −1 ). Biosolids application increased the biomass of sorghum, rapeseed, and ryegrass up to 14.0, 11.9, and 4.1 t ha −1 eq, respectively. Mixing sawdust with biosolids resulted in a growth response similar to biosolids treatments in rapeseed but nullified the effect of biosolids in sorghum. Urea fertilization provided insufficient nutrients to promote rapeseed growth and seed production, whereas seed yields after biosolids application were 2.5 t ha −1 . Biosolids and biosolids‐sawdust application enhanced plant quality by increasing element concentrations, especially Zn, and potentially toxic elements (Cd, Cr, Ni) did not exceed food safety standards. An application of 50 t ha −1 of biosolids, equivalent to 1250 kg N ha −1, did not exceed current soil limits of Cu, Zn, and Cd and hence was effective in rebuilding soil without accumulating contaminants. The effect of mixing sawdust with biosolids varies with plant species but can further enhance plant nutrient quality in biomass and seeds, especially P, Cu, Zn, Mn, Fe, S, and Na. Core Ideas: Biosolids application showed potential for Zn enrichment in all plant species. Biosolids and sawdust applied to soil enables growth of rapeseed in low‐fertility soil. Toxic elements like Cd were not increased to levels dangerous for human health. Biosolids and sawdust increased seed quality and hence potentially plant products.